Pemberdayaan Ekonomi Masyarakat Desa Ngilo-ilo Melalui Inovasi Olahan Singkong - Mohammad Ridwan; Ananda Citra Apriliana Sari; Anisa Maya Umri Hayati (Institut Agama Islam Negeri Ponorogo, 2023)
The lack of creativity makes cassava one of the most abundant natural resources in Ngilo-ilo village, but it has not been innovated into a product that is more varied and has a high selling value. Therefore, in the program to improve the economic welfare of the people of Ngilo-ilo Village through the innovation of processed cassava products, the core program activities of the Community Service Lecture (KPM) aim to improve the economic welfare of the community by increasing added value and competitiveness in cassava management. The method in this activity uses a demonstration of the method in the form of training, namely the practice of making food with the main ingredient of cassava. In the practice of processing cassava, it produces three food product innovations, including gethuk sultan, cassava rolls, and cassava croquettes.